2016
DOI: 10.31989/ffhd.v6i11.295
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrite: from menace to marvel

Abstract: ABSTRACT:The health benefits of nitrite are now indisputable when administered in a clinical setting for specific diseases. Currently, most published reports identify the production of nitric oxide (NO) as the mechanism of action for nitrite. Basic science, in addition to clinical studies, demonstrate that nitrite and/or nitrate cannot restore NO homeostasis as an endothelium independent source of NO that may be a redundant system for endogenous NO production. Nitrate must first be reduced to nitrite by oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The negative health effects of nitrates and nitrites are commonly described in the literature [9][10][11]. On the other hand, in recent years, various benefits of the supply of nitrates with the diet have been indicated, in particular on the function of the cardiovascular system [12,13]. These benefits are related to the supply of nitric oxide, which have a positive effect on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…The negative health effects of nitrates and nitrites are commonly described in the literature [9][10][11]. On the other hand, in recent years, various benefits of the supply of nitrates with the diet have been indicated, in particular on the function of the cardiovascular system [12,13]. These benefits are related to the supply of nitric oxide, which have a positive effect on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…The predictions that dietary intake of nitrate and/or nitrite may increase the risk of gastric cancer, extrapolated from animal studies, have not been substantiated epidemiologically [ 44 , 50 ]. On the contrary, several studies have observed the beneficial effects of dietary nitrate supplementation on, for example, blood pressure and endothelial function, demonstrating that NO homeostasis can be restored by nitrite and/or nitrate independent from enzymatic NO sources and may represent a further system for endogenous NO production [ 51 , 52 , 53 ].…”
Section: Nitric Oxide and Nitric Oxide Derivatesmentioning
confidence: 99%
“…However, it is known that nitrite is capable of causing severe methemoglobinemia with a high mortality following the intake of sodium nitrite, which is often misused for self-poisoning [ 54 ]. However, nitrite, when administered in a clinical setting for specific diseases, reveals health benefits because most of the published reports identify NO production as the mechanism of action for nitrite applications [ 52 ].…”
Section: Nitric Oxide and Nitric Oxide Derivatesmentioning
confidence: 99%
“…NO 2 − also produces NO and bioactive NO in the blood and tissues. The reduction of nitrate and nitrite to NO is called the nitrogen oxide cycle [ 72 , 73 ] ( Fig. 6 ).…”
Section: Physiological Action Of Nitric Oxide In the Bodymentioning
confidence: 99%